Covid 19, Ketimpangan dan Kemiskinan di Pedesaan Indonesia - Sjaf, Sofyan (Sodality: Jurnal Sosiologi Pedesaan, 2023)
The Covid-19 pandemic has had an impact on inequality and poverty in rural Indonesia. This study aims to identify inequality and poverty during the Covid-19 pandemic, as well as program policies for poor families after the Covid-19 pandemic in rural Indonesia. The combination of quantitative and qualitative methods with the Drone Participatory Mapping (DPM) approach is the preferred method used by researchers to obtain Precision Village Data (PVD). From this data, the researcher used the Lorenz Curve to determine the inequality and poverty of families in three villages (Sibandang, Cikarawang and Tegallalang). The results showed that the three research villages were in low inequality conditions (Sibandang Village with the typology of plantation village = 0.39; Cikarawang Village with the typology of food crops village = 0.36; and Tegallalang Village with the typology of rice field village = 0.35) during the Covid-19 pandemic. From this inequality, every poor family in rural Indonesia has a different income. Therefore, the policy to restore the condition of poor families in rural Indonesia must address three main aspects: education, employment and income.